ITERATIVE ACTION IN CRIMINAL LAW - Salas Porras , Ricardo (2025)
In the following pages the topic of the iterative action, the natural unity of action, the legal unity, the single infringement and the plurality of infringements will be addressed. The iterative action, which is the one carried out through homogeneous, successive and equivalent acts, each of which fills the criminal category, constitutes a single action and, unless there is a plurality of victims in highly personal interests, a single infraction.